Forest cover changes and the shift of forest management in Aurora province - Isorena, Trina G.; Nantes, Doracie Zoleta (Quezon City Department of Geography, Social Science and Philosophy, University of the Philippines Diliman, 2008)
Commercial logging through the Timber License Agreement (TLA) was the primary system implemented by the Philippines to manage its forest resources from 1950s up to early 1990s. This period was associated with high rates of deforestation and increasing number of environmental disasters experienced by Filipinos. In the following years, pressure from the different sectors of the Philippine society pushed the government to shift the paradigm of forest management policies in the country. The changes instituted focused on expanding collaborative management of forest and forestlands resources by the Department of Environment and Natural Resources with indigenous peoples, forest resource dependent communities, local government and private groups. Most significant among the changes was the institution of new forms of resource tenure which transformed the once Timber License Agreement (TLA)- dominated forestlands of Aurora Province. Primary beneficiaries of these changes are the communities who were given tenure on the public lands they occupy.
Thesis (M.S. Geography)--University of the Philippines Diliman
Keywords: Forest management -- Philippines -- Aurora (Quezon).